Realidade Virtual e Jornalismo Imersivo: anotação dinâmica de peças noticiosas em vídeo 360º - João Pedro de Oliveira Marques (2016)
The spread of virtual reality systems and immersive content has been growing substantially due to technological progress and cost reductions. From all the technologies employed in virtual reality systems, 360º video is one that currently presents unique conditions to be widely used by various industries - especially for communication purposes. This is due to the simplification of production and distribution of 360º video content, thanks to the availability of consumer-oriented capture devices, the creation of web-based visualization solutions (such as YouTube) and the adaptation of current technologies like the smartphone for this purpose (for instance, Google Cardboard, a low-cost, simple to manufacture and easy to distribute system). From the various areas that can benefit from the usage of virtual reality systems, the communication field is ripe for innovation in the way that narratives are built. In the case of journalism - referencing the concept of immersive journalism - 360º video technology is one of the most used mediums by several media outlets. Institutions such as The New York Times or ABC News present news content in this format, reaping the aforementioned benefits. This kind of news content, whose innovative role should be highlighted, is still being studied in the field of journalism, as a need of clearly defined rules and good practices arises in order to better harness the capabilities of 360º video. After an analysis of some content in this medium, some potential ambiguity sources were detected for the final consumer, regarding the identification of visual points and locations, as well as readable subtitling. A list of potential visual annotation paradigms (not to be traditionally edited on top of currently existing video information but to be applied on runtime) was made, from which two paradigms were developed as a prototype with clips from existing 360º video news content. It is hypothesized that, with the addition of dynamic information that follows the user's visual field, it is possible to mitigate ambiguities regarding location information in the space of a 360º video, as well as improving general comprehension of the video content by the user.